Factors associated with mortality in severe SARS-CoV-2 infection in a Peruvian hospital - Amado-Tineo, José (2021)
Objetive: To determine factors associated with mortality in patients with severe SARS-CoV-2 disease. Materials and methods: Retrospective study in patients older than 18 years hospitalized with severe disease (peripheral oxygen saturation <93% or radiological lung involvement > 30%) and a positive RT-PCR nasopharyngeal swab; in the Rebagliati hospital between March and May 2020. We reviewed electronic medical record, results of admission studies (laboratory and radiological) and treatment received. Bivariate and multivariate analysis were performed using cox regression. Results: 337 patients were studied, 215 of them died (63.8%). 72.1% were male, mean age was 63.6 years (SD 15.3), time of disease evolution was 7.4 days, hospital stay 10.3 days, and 48.8% were on mechanical ventilation. Multivariate analysis found significance in age > 60 years (HR 1.76, IC95% 1.26-2.45), history of type 2 Diabetes (HR 1.63, IC95% 1.14-2.32), pulmonary involvement > 75% (HR 1.87, IC95% 1.37-2.56), leukocytes > 14000 x mm3 (HR 1.59, IC95% 1.15-2.20), serum albumin < 4.0 g/dL (HR 2.49, IC95% 1.30-4.75) and lactate > 1.5 mmol/L (HR: 1.766 IC95% 1.25-2.49). Conclusions: Age older than 60 years, type 2 diabetes mellitus, severe pulmonary involvement, leukocytosis, low albumin, and high lactate at admission are factors associated with mortality in patients with severe SARS-CoV-2 disease.